ANALISIS OPTIMALISASI PRODUKSI DURIAN SINAPEUL (Durio zibethinus Murr) DENGAN MENGGUNAKAN PENDEKATAN LINEAR PROGRAMMING - Winda Rahmah Ilahi; Ida Marina; Kosasih Sumantri (AGRIVET JOURNAL, 2020)
ABSTRACTDurian Sinapeul is one of the local superior fruits in Majalengka. To be able to achieve optimum production results and profits, it is necessary to know the level of production combination. Therefore, this study aims to analyze the optimization of production output by using analysis techniques linear programming. The selection of respondents was carried out using a probability sampling of 35 respondent farmers in the Saritani Farmers Group. The results showed that the actual conditions were far different from the optimal conditions in which the optimal scheme included only durian sinapeul bokor varieties with an optimal production of 324 items. While other varieties such as officers and cangpis if forced into the optimal scheme there are additional production costs or reduced profits for the value of the reduced cost. For siriwig varieties, if included in the optimal scheme does not effect to increasing production costs or decreasing profits. The obstacles faced by durian sinapeul farmers to maximize profits is in the form of the use of production factors in the form of excess resources.  Keywords: durian sinapeul, optimization, production, linear programming